P033 Colonic Histoplasmosis Mimicking Metastatic Colon Cancer in a Patient With Ulcerative Colitis on Infliximab. (December 2019) - Henke, Jonathan; Fathallah, Jihan; Hinthorn, Daniel; Wetzel, Louis; Da, Zhang; Bonino, John
Abstract : BACKGROUND: Histoplasma capsulatum is a dimorphic fungus that may cause a self-limited respiratory infection in immunocompetent individuals. Immunosuppressed individuals, however, are at increased risk for disseminated disease. We report a case of a patient presenting with ulcerative colitis on chronic anti-TNF therapy, presenting with sinister-appearing colonic ulcers and abnormal CT imaging suggesting omental disease. CASE SUMMARY: A 43 year old man with a 12 year history of ulcerative colitis was referred to the university medical center with progressive abdominal pain and distention. He had undergone a previous outside colonoscopy showing segmental inflammation in the ascending colon with a discrete ulceration. Biopsies were non-diagnostic. Laboratory studies showed a normal leukocyte count but marked monocytosis. Cross-sectional imaging demonstrated multiple enlarged mesenteric lymph nodes and omental soft tissue thickening, suggestive of possible omental metastatic disease. Of note, chest imaging was unremarkable. The patient underwent a repeat colonoscopy, which showed a "single 2 cm discrete ulcer with heaped-up edges" in the distal ascending colon. The lesion was biopsied and sent for histology, flow cytometry, and immunohistochemical stains. Histology disclosed active colitis and cryptitis with mucosal ulceration and epithelioid granulomas. There was no evidence of malignancy or dysplasia. Viral inclusions were not visualized. Further workup, including fungal blood cultures and serum (1 → 3)-β-D-glucan fungal assay, was negative. Serum and urine Histoplasma antigens were measured and reported as "weakly positive, but below the level of quantification." Due to the uncertainty of the diagnosis, percutaneous CT-guided omental biopsies were obtained and showed no evidence of lymphoma or malignancy. Fungal stains (GMS) of the repeated colonic ulcer biopsies were requested and ultimately confirmed the diagnosis of colonic Histoplasmosis. The patient was treated with 2 weeks of intravenous amphotericin, followed by oral itraconazole for one year. Follow-up CT scans demonstrated resolution of his abdominal lymphadenopathy and inflammatory stranding. A subsequent colonoscopy showed complete resolution of the ulcer. He has had no recurrence of Histoplasmosis or similar colonic lesions based on follow-up with both gastroenterology and infectious disease clinics. CONCLUSION: GI histoplasmosis as a manifestation of disseminated disease is not well characterized in the immunosuppressed IBD population. Atypical features of our case included the absence of abnormal chest imaging, which is estimated to occur in 70% of immunocompromised patients with dissemination. Additionally, the patient's associated serologic and urinary testing was initially equivocal, making diagnosis difficult. Disseminated histoplasmosis should be considered in immunocompromised IBD patients presenting with malignant appearing colonic ulcerations and nodular omental thickening on CT, even in the absence of strong supporting laboratory and radiologic data.